Three-dimensional rotation of the object image around any arbitrary axis - Фесенко, М. Б. (Problems of Informatization and Control, 2004)
On the basis of classical algorithm new variant of the formula derivation for three- dimensional rotation around of arbitrary axis is proposed which can be used in practice for automation of account of flights of aircrafts, rotary moving of robots, computer graphic objects transformation and image processing